2005
DOI: 10.1021/la0513196
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Shape and Mobility of Colloidal Gold Nanorods with Electrospray and Differential Mobility Analyzer Methods

Abstract: The potential of the electrospray technique in analyzing the structure of nonspherical colloidal particles that are below 100 nm in volume-equivalent diameter was demonstrated by online size measurement using a differential mobility analyzer (DMA) with a condensation nucleus counter (CNC) system. The measured mobility of gold nanorods was confirmed by electron microscope images and the theoretical calculation of particle mobility using the dynamic shape factor and slip correction factor. To evaluate the mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…When considering the relationship between particle mobility diameter and particle shape it is worth reminding that changes in particle shape can result in large changes in mobility diameters, as it was illustrated in the recent study by Song et al (2005), where the particles' mobility diameter decreased from 55 nm to 25 nm as a result of the change in their shape; from rod-like with an aspect ratio of 5.6 to nearly spherical. Since the present study focuses only on changes in particle orientation, while the particle shape remains constant, the corresponding changes in mobility diameter are expected to be smaller.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When considering the relationship between particle mobility diameter and particle shape it is worth reminding that changes in particle shape can result in large changes in mobility diameters, as it was illustrated in the recent study by Song et al (2005), where the particles' mobility diameter decreased from 55 nm to 25 nm as a result of the change in their shape; from rod-like with an aspect ratio of 5.6 to nearly spherical. Since the present study focuses only on changes in particle orientation, while the particle shape remains constant, the corresponding changes in mobility diameter are expected to be smaller.…”
Section: Introductionmentioning
confidence: 98%
“…From these studies they were able to deduce the orientation dependent DSFs for the two PSL agglomerates. In a very recent publication Song et al (2005) described the results of a very elegant experiment designed to investigate the relationship between the mobility diameter of gold nanoparticles and their shapes. The changes in the shape and the mobility diameters of gold nanoparticles as a function of temperature were observed using Scanning Electron Microscopy (SEM) and the DMA.…”
Section: Introductionmentioning
confidence: 99%
“…Though several techniques are available to quantify the length distributions of nanorods and nanotubes, ES-DMA remains competitive (see Section 3 for a detailed comparison). Several authors have reported the characterization of rod-or tube-like particles, such as, gold nanorods and multi-walled carbon nanotubes [Baron et al, 1994;Chen et al, 1993;Deye et al, 1999;, 2006, 2007aMoisala et al, 2005;Song et al, 2005]. Song, et al, used a shape factor analysis to convert the average mobility diameter into the average length of gold nanorods.…”
Section: Nanotubes and Nanorodsmentioning
confidence: 99%
“…NSBs may include long-chain molecules, nanorods and nanotubes. Applications range from drag on cylinders or chains of spheres [1], size classification of fiberous aerosols [2][3][4][5][6], ion mobility of long-chain molecules and biomolecules [7][8][9], gas-phase synthesis, separation and characterization of nanotubes and nanorods [10][11][12][13][14][15][16][17][18][19][20], to transport properties of long-chain hydrocarbons in reacting flows [21][22][23].…”
Section: Introductionmentioning
confidence: 99%